PERKEMBANGAN UMKM SANDAL DI DESA WEDORO : STUDI KASUS PENGGUNAAN ANALISIS SWOT DALAM STRATEGI PENGEMBANGAN UMKM DI ERA MODERN - Uswatun Khasanah; Ries Dyah Fitriyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of the era in this modern era has an impact on all sectors in Indonesia. One of the sectors affected is the MSME economic sector. The types of MSME in Indonesia are very diverse, one of the focuses of MSMEs in this study is the sandal MSME in Wedoro, Sidoarjo. The researcher's goal is to find out how the strategies of MSME actors are in this modern era and analyze the strategies of MSME actors using SWOT analysis. This study uses a qualitative method, namely data collection techniques by conducting interviews, observations, or documentation. In this SWOT analysis we can find out what are the strengths, weaknesses, opportunities and threats faced by sandal actors in this modern era. The modern era in MSMEs has a fairly large role, with the development of advanced technology, sandal MSME actors in Wedoro Village can take advantage of it by buying and selling on online platforms such as Instagram, Shopee and so on. With this SWOT analysis, it can be expected as an evaluation for sandal MSME actors to provide better innovation.